2021
DOI: 10.1002/app.51675
|View full text |Cite
|
Sign up to set email alerts
|

Granitic quarry waste as a dual functional filler for high density polyethylene‐based composites: Mechanical and microwave absorbing properties

Abstract: Cost-effective polymeric composites were successfully prepared by melt blending granitic quarry waste (GQW) with high-density polyethylene (HDPE). The GQW is a waste generated during the production of manufacture fine aggregates (MFA) from crushed gneiss rock and contains significant amount of mica with iron in its structure. Different sieving and milling procedures were employed. The materials were characterized by mechanical and dynamicmechanical properties and scanning electron microscopy. Moreover, the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Similar observations were reported with for PE composites filled with commercial talc 8 and sandalwood. 52 In the case of PE filled with granitic waste, 4 the improvement in dynamic storage modulus was observed mainly in the glassy region, while at higher temperatures the filler effect on stiffness was negligible.…”
Section: Dynamic Mechanical Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were reported with for PE composites filled with commercial talc 8 and sandalwood. 52 In the case of PE filled with granitic waste, 4 the improvement in dynamic storage modulus was observed mainly in the glassy region, while at higher temperatures the filler effect on stiffness was negligible.…”
Section: Dynamic Mechanical Thermal Analysismentioning
confidence: 99%
“…In addition, significant improvements in the performance of commercial polymers can be achieved, since inorganic fillers can reasonably be integrated into thermoplastic matrices, allowing for optimization of specific properties 3 . In fact, Moura et al 4 reported that the incorporation of granitic quarry waste into polyethylene led to improvements on mechanical performance, associated with interesting microwave absorbing properties. It has also been shown that marble waste is promising alternative filler, capable of improving the flexural strength, elastic modulus and wear resistance of different thermoplastic matrices 5–7 …”
Section: Introductionmentioning
confidence: 99%